Study on snoring habit in healthy population of Eastern Odisha - Devi, Ellora; Sahu, Samir; Ray, Subhashree (International Journal of Medical Research and Review, 2016)
Introduction: Snoring caused due to relaxation of upper airway tract leading to partial closure of the respiratory passage and characteristic snoring sound with reduced oxygen entry into lungs. Estimates of prevalence of snoring ranges from 5-44% of the general population. As per the gender distribution 24 - 50% men &14 - 30% women had snoring habits. Methods: It was single Centre cross sectional study done by Department of Physiology, IMS & SUM Hospital in apparently healthy attendants accompanying patients using ‘Snore Survey’ questionnaire, Berlin Questionnaire. Results: There were 550 participants. Out of which 59.72% of men, 40.20% of women snored, 47.46% from both sexes were unaware of their snoring habit. 25.6% of all snorers confirmed daytime sleepiness. Prevalence of snoring increased in both sexes with increase in age. In males, the highest prevalence rate of snoring was obtained in the age group 50 -59, out of which 19.5% had moderate and 14.6% had habitual snoring.10.6% of the males in the age group 55–69 years had clinically suspected Obstructive Sleep Apneas. For females, the highest prevalence rate of snoring occurred at age 40-49years with 17.8% having moderate and 7.1% habitual snoring, whereas clinically suspected Obstructive Sleep Apneas among the female was 8%. Conclusion: Snoring a commonly ignored problem in our society, unless treated leads to risk of metabolic syndrome, Diabetes, CVS diseases like Hypertension, Arrhythmias& death.